Study of Retinal Nerve Fiber Layer Thickness by Optical Coherence Tomography in Primary Open Angle Glaucoma, Glaucoma Suspect and Normal Nepalese Population - Godar, Srijana Thapa; Kaini, KR (Nepal Medical College Journal, 2020)
The measurement of retinal nerve fiber layer thickness can help significantly in the early diagnosis of glaucoma and monitoring of its progression. The objective of this study was to compare the retinal nerve fiber layer (RNFL) thickness by optical coherence tomography in primary open angle glaucoma, glaucoma suspects and normal Nepalese population. This was a hospital based cross-sectional study conducted in the Ophthalmology Out Patient Department of Manipal Teaching Hospital, Pokhara. Total 100 numbers of subjects (40 primary open angle glaucoma, 30 glaucoma suspects and 30 normal people) were evaluated. Complete ophthalmological examinations including tonometry, gonioscopy, optical coherence tomography, perimetry were performed. Statistical analysis was carried out using Epi-info 7. The result showed that the average retinal nerve fiber layer (RNFL) thickness was 70.22±12.07μm in right eye and 69.42±11.53μm in left eye in primary open angle glaucoma (POAG), 88.87±10.39μm in right eye and 88.73±9.59μm in left eye in glaucoma suspects (GS) and 94.40±9.21μm in right eye and 94.73±6.76μm in left eye in normal group respectively. The mean RNFL thickness was statistically significant in all three comparison groups except in nasal quadrant. The mean RNFL thickness was statistically significant in two comparison groups except in GS-Normal (nasal and temporal quadrant), GS-POAG (left nasal quadrant) and Normal-POAG (left nasal quadrant). The study concluded that the RNFL thickness is lower in POAG as compared to glaucoma suspects and normal group in the Nepalese population.